Decoding Neurological Mysteries: The Potential Impact of Endogenous Retroviruses on Brain Health - Jiaqi Li; Liyong Liao; Xixi Liu; Yueyan Zhu; Daijing Sun; Chenchun Zhang; Yan Jiang (Stress and Brain, 2024)
Endogenous retroviruses (ERVs), remnants of ancient viral invasions, make up a significant part of the mammalian genomes. ERVs are typically held in check by complex epigenetic mechanisms, which serve to limit their expansion and potential adverse effects on the genome. However, ERVs can become aberrantly activated in response to stressful challenges, contributing to progression in pathological conditions, including cancer, inflammation, auto-immune disorders, and aging, through various mechanisms. Notably, ERV activation is also detected in the brain and is increasingly recognized as an important factor in neuropsychiatric disorders. In this review, we encapsulate the general understanding of ERVs in both physiological and pathological states and compiled evidence for ERV activation across a spectrum of neuropsychiatric disorders, along with current studies exploring the underlying mechanisms. Despite the accumulating body of evidence, research in this field remains in its infancy and faces substantial challenges. Further studies are warranted to enhance our understanding of ERV activation mechanisms and their roles in neuropsychological conditions, potentially contributing to the development of innovative therapeutic interventions.